Analisis Strategi Pemasaran Digital Mawwah Hijab dalam Mengkomunikasikan Nilai Halal di Instagram dan TikTok - Adinugroho, Prasetyo (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
The advancement of the digital era has shifted marketing strategies to platforms like Instagram and TikTok, which function not only as promotional media but also as tools to communicate a product's core values, including halal value. This descriptive qualitative research aims to analyze the Marketing Mix 4P (Product, Price, Place, Promotion) strategy in communicating halal value digitally, using a case study of the Indonesian hijab fashion brand, Mawwah Hijab (@mawwahhijab). Data was collected through content analysis of the brand's profile and posts on Instagram (36K followers) and TikTok (57K followers). The study's findings reveal that Mawwah Hijab effectively integrates all four 4P elements with halal value. Product is communicated by emphasizing MUI halal certification and modest designs, visualized through aesthetic content. Price is set competitively (IDR 27,900 – IDR 72,900) and promoted with a